Design and Validation of Soft Sliding Structure with Adjustable Stiffness for Ankle Sprain Prevention - Ham, Seoyeon; Paing, Soe Lin; Kang, Brian Byunghyun; Lee, Hyunglae; Kim, Wansoo (IEEE robotics and automation letters, 2024)
This study presents the design and validation of a soft sliding stiffness structure with a soft-rigid layer sliding mechanism. It aims to mitigate ankle sprains and address the progression of chronic ankle instability by providing stiffness support. The soft-rigid layer sliding mechanism of the structure is designed to achieve a wide range of stiffness while maintaining a compact form factor. The structure incorporates rigid retainer pieces within each layer, which allows for sliding within a hollow cuboid structure and enables modulation of stiffness. An analytical model is presented to investigate the variations in stiffness resulting from the different sliding states. The stiffness characteristics of the structure were validated through both bench tests and human subject tests. The gradual sliding of the structure's layer resulted in an increase in stiffness, aligning with the analytical model's predictions. At the most rigid stage (0% alignment), the stiffness exhibited a significant increase of 111.1% compared to the most flexible stage (100% alignment). Additionally, the human subject testing demonstrated a stiffness increase of up to 93.8%. These results underscore the potential applicability of the soft sliding structure in ankle support applications.